2016
DOI: 10.3389/fpsyg.2016.00324
|View full text |Cite
|
Sign up to set email alerts
|

Anomalous Cerebellar Anatomy in Chinese Children with Dyslexia

Abstract: The cerebellar deficit hypothesis for developmental dyslexia claims that cerebellar dysfunction causes the failures in the acquisition of visuomotor skills and automatic reading and writing skills. In people with dyslexia in the alphabetic languages, the abnormal activation and structure of the right or bilateral cerebellar lobes have been identified. Using a typical implicit motor learning task, however, one neuroimaging study demonstrated the left cerebellar dysfunction in Chinese children with dyslexia. In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 96 publications
0
12
0
Order By: Relevance
“…Notably, when investigating anatomical structure, Yang, Yang, Chen, Zhang, and Bi observed reduced gray matter volume in the left cerebellum of Chinese-speaking children with DD relative to controls. 31 Feng et al further explored cerebrocerebellar functional connectivity and suggested atypical connectivity patterns existed between the left cerebellum and the left fusiform gyrus during orthographic processing, whereas increased connectivity between the right cerebellum and the left supramarginal gyrus was found during phonological processing. 32 However, in the present study, the integrity of the right cerebellar tracts was significantly associated with the children's performance of character recognition.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, when investigating anatomical structure, Yang, Yang, Chen, Zhang, and Bi observed reduced gray matter volume in the left cerebellum of Chinese-speaking children with DD relative to controls. 31 Feng et al further explored cerebrocerebellar functional connectivity and suggested atypical connectivity patterns existed between the left cerebellum and the left fusiform gyrus during orthographic processing, whereas increased connectivity between the right cerebellum and the left supramarginal gyrus was found during phonological processing. 32 However, in the present study, the integrity of the right cerebellar tracts was significantly associated with the children's performance of character recognition.…”
Section: Discussionmentioning
confidence: 99%
“…The neural anomalies found in studies of RD in Chinese readers vary in terms of their consistency with those identified in alphabetic languages. For example, while some researchers found that Chinese RD children show atypical anatomy in left TPC (Xia, Hoeft, Zhang, & Shu, ) and the cerebellum (Yang, Yang, Chen, & Bi, ), similar to that reported in studies that have examined English RD, others report anomalies in areas such as the left middle frontal gyrus (Siok, Niu, Jin, Perfetti, & Tan, ), which are not associated with RD in studies of alphabetic languages. Notably, Chinese RD has been specifically associated with anomalies in the left middle frontal gyrus and the superior parietal lobule, which may reflect larger semantic and visuospatial demands, and heavier working memory load associated with the logographic system (Siok, Perfetti, Jin, & Tan, ; Siok, Spinks, Jin, & Tan, ; Siok et al, ; Xu, Yang, Siok, & Tan, ).…”
Section: Cross‐linguistic Comparisonsmentioning
confidence: 72%
“…Several studies in DD have investigated differences in brain structure when compared to unimpaired readers using voxel-based morphometry, with or without functional MRI (Brambati et al 2004 ; Brown et al 2001 ; Dole et al 2013 ; Eckert et al 2005 , 2016 ; Evans et al 2014 ; Hoeft et al 2007 ; Jednoróg et al 2014 , 2015 ; Krafnick et al 2014 ; Kronbichler et al 2008 ; Menghini et al 2008 ; Pernet et al 2009a , b ; Raschle et al 2015 ; Silani et al 2005 ; Siok et al 2008 ; Steinbrink et al 2008 ; Tamboer et al 2015 ; Vinckenbosch et al 2005 ; Xia et al 2016 ; Yang et al 2016 ).…”
Section: Discussionmentioning
confidence: 99%